2019
DOI: 10.1002/bbb.1976
|View full text |Cite
|
Sign up to set email alerts
|

The costs of sugar production from different feedstocks and processing technologies

Abstract: Sugar production is essential for the production of foods, biochemicals, and biofuels via biochemical or catalytic routes. Sugar‐containing crops, and starch‐based and cellulosic feedstocks are resources for sugar production via juice extraction, starch saccharification, and pretreatment and hydrolysis, respectively. Technologies have been developed to attain a high sugar yield; however, production costs are a major consideration in commercializing newly developed approaches to the production of sugars. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 61 publications
(265 reference statements)
1
48
1
1
Order By: Relevance
“…Sugars are a common carbon and energy source for microbial cultivations and oleaginous heterotrophs can consume them simultaneously or sequentially [34]. Using sugar crops for microbial oil production is simpler than starchy or cellulosic biomass, as pre-treatment and saccharification are not required [35], as such the cheapest source of sugars are still first generation sugarcane [23]. As such our prospective microbial lipid production plant was assumed to be adjacent to a sugarcane mill from which sugars from sugarcane juice are provided.…”
Section: Selection Of Carbon Source and Plant Locationmentioning
confidence: 99%
“…Sugars are a common carbon and energy source for microbial cultivations and oleaginous heterotrophs can consume them simultaneously or sequentially [34]. Using sugar crops for microbial oil production is simpler than starchy or cellulosic biomass, as pre-treatment and saccharification are not required [35], as such the cheapest source of sugars are still first generation sugarcane [23]. As such our prospective microbial lipid production plant was assumed to be adjacent to a sugarcane mill from which sugars from sugarcane juice are provided.…”
Section: Selection Of Carbon Source and Plant Locationmentioning
confidence: 99%
“…The pretreatment technology chosen affects operating costs related to utility consumption (steam, electricity), labor and wastewater treatment. Feedstock and chemical costs are similar among various pretreatment options and these make up 60% of the total production costs [8]. An economic comparison of leading pretreatment technologies, using the same process assumptions, found that LHW pretreatment has higher production cost than dilute acid and ammonia fiber expansion (AFEX) due to lower ethanol yields and higher energy inputs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Feedstock and chemical costs are similar among various pretreatment options and these make up 60% of the total production costs [8]. An economic comparison of leading pretreatment technologies, using the same process assumptions, found that LHW pretreatment has higher production cost than dilute acid and ammonia fiber expansion (AFEX) due to lower ethanol yields and higher energy inputs [8,9]. However, the pretreatment operating conditions play an important role in determining production cost, especially utility cost.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations